Ongoing controversies surrounding cardiac remodeling: is it black and white—or rather fifty shades of gray? - Spaich, Sebastian; Katus, Hugo A.; Backs, Johannes (Frontiers in Physiology, 2015)
Cardiac remodeling describes the heart’s multimodal response to a myriad of external or intrinsic stimuli and stressors most of which are probably only incompletely elucidated to date. Over many years the signaling molecules involved in these remodeling processes have been dichotomized according to a classic antagonistic view of black and white, i.e. attributed either a solely maladaptive or entirely beneficial character. By dissecting controversies, recent developments and shifts in perspective surrounding the 3 major cardiac signaling molecules calcineurin (Cn), protein kinase A (PKA) and calcium/calmodulin-dependent kinase II (CaMKII), this review challenges this dualistic view and advocates the nature and dignity of each of these key mediators of cardiac remodeling as a multilayered, highly context-sensitive and sophisticated continuum that can be markedly swayed and influenced by a multitude of environmental factors and crosstalk mechanisms. Furthermore this review delineates the importance and essential contributions of degradation and proteolysis to cardiac plasticity and homeostasis and finally aims to integrate the various aspects of protein synthesis and turnover into a comprehensive picture.